How China opened its door : the political success of the PRC's foreign trade and investment reforms - Shirk, Susan L. (Washington, D.C. : Brookings Institution, 1994)
China's transformation from a virtually closed economy to a major trading nation is an incredible success story. Since 1979 the country has changed its policies to promote increased foreign trade and investment, thereby attracting more direct investment to China than to any other developing country in recent years. What brought about this change? How, after thirty years of being walled off from the world economy, did China open its door? This book, part of the Brookings Integrating National Economies series, tells the story of how China ended its long-held policies of economic isolationism and rejoined the world economy in the decade and a half between 1979 and 1994. It shows how China's transformation into a world trading power was achieved remarkably without any major alteration in the country's communist political system. Susan L. Shirk describes the reform strategy and explains why such a turnaround was possible in China but not in the Soviet Union.
Shirk's analysis details the political logic behind the economic reform, illustrating how China's leaders were able to win support for reform policies among Communist Party and government officials. Despite strong vested interests in the status quo, the communist government successfully adopted reforms through gradualism, administrative decentralization, and ad hoc, particularistic negotiating with individual subordinates. Shirk explains these distinctive features of China's path to reform.
China has achieved shallow integration with great success. Whether deeper integration with the world economy will automatically follow remains unclear. Shirk concludes that China will not be able to achieve reform in the areas of deep integration - intellectual property rights, environmental protection, and labor treatment - in the same way it achieved shallow integration. She argues that imposing international standards will require rapid enforcement, central regulation, and uniform rules. If China can meet these challenges, only then will the country successfully move toward greater openness and deeper international integration.
1. Economic Reform without Political Reform -- 2. The Pre-reform System. The Closed Command Economy -- 3. China's Political Institutions. Who's in Charge? The Communist Party and the Government. Reciprocal Accountability and Leadership Competition. The Policy Process: Delegation by Consensus. The Chinese Version of Communist Institutions -- 4. Patterns in Reform Policies. Gradualism. Administrative Decentralization. Particularistic Contracting -- 5. Foreign Economic Reform Policies. Regional Policies toward Foreign Investment. The Decentralization of Foreign Trade Authority -- 6. Opening the Door Wider. Reforming the Foreign Exchange Regime. Opening the Domestic Market -- 7. The Political Challenge of Deeper Integration. Intellectual Property Rights. Environmental Protection. Labor Standards. Difficulties of Deep Integration -- Comments / Harry Harding.
Includes bibliographical references (pages 111-114) and index.
Print version record.
JSTOR
Keywords: China -- Commercial policy; China -- Economic policy -- 1976-2000.; Chine -- Politique économique -- 1976-2000.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Politique commerciale; Politique économique.; Chine; Commercial policy; Economic policy; China; Außenhandelspolitik; China; Economische hervormingen; Handelspolitiek; BUSINESS & ECONOMICS / International / General; 1976-2000; Geschichte 1979-1994.